Flavored cashew nut butter - Lima, Janice Ribeiro; Duarte, Elianne de Alencar (Pesquisa Agropecuaria Brasileira, 2006)
Characteristics of cashew nut butter with added chocolate and cinnamon were evaluated. Formulations were obtained by grinding ingredients onto a homogeneous paste, which was analyzed for moisture, pH, ash, protein, fat, acid value, water activity, texture and sensory acceptance. Products obtained showed low water activity (<0.32) as well as moisture content (<1.4%). Fat (45.3 to 49.1%) and protein (15.4 to 16.3%) content were high. Nut butter formulations showed good sensory acceptance (82.9 to 100.0%) and purchase intent (60.0 to 80.0%) by the tasters.